Hematopoietically expressed homeobox (HHEX) gene polymorphism (rs5015480) is associated with increased risk of gestational diabetes mellitus. Issue 6 (30th November 2016) - Tarnowski, M.; Malinowski, D.; Safranow, K.; Dziedziejko, V.; Czerewaty, M.; Pawlik, A.
Abstract : Gestational diabetes mellitus (GDM) is a metabolic disorder that occurs during pregnancy. HHEX and PROX1 are genetic loci associated with diabetes mellitus type 2. HHEX and PROX1 play significant roles in carbohydrate intolerance and diabetes because these transcription factors may be involved in the regulation of insulin secretion and in glucose and lipid metabolism. The aim of this study was to examine the association between HHEX (rs5015480) and PROX1 (rs340874) gene polymorphisms and GDM. This study included 204 pregnant women with GDM and 207 pregnant women with the normal glucose tolerance (NGT). The diagnosis of GDM was based on a 75‐g oral glucose tolerance test at 24–28 weeks' gestation. There was a statistically significant prevalence of the HHEX rs5015480 CC genotype and C allele among women with GDM (C vs T allele, p = 0.021, odds ratio OR = 1.40, 95% CI: 1.05–1.87). Statistically significant higher increase of body mass and BMI during pregnancy was found in women with the HHEX rs5015480 CC genotype. The results of our study suggest an association between the HHEX gene rs5015480 polymorphism and risk of GDM. The HHEX gene rs5015480 C allele may be a risk allele of GDM that is associated with increased BMI during pregnancy. Abstract :